Modular development of data-centric applications for edge devices = Modułowy rozwój aplikacji zorientowanych na dane dla urządzeń brzegowych - Zielony, Przemysław; Piotrowski, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
With the dynamic development of the sensor network technology, there is a growing need for effective software design that is scalable and flexible. This work presents a modular structure based on tinyDSM, enabling the connection of various adapters and services. This approach streamlines the development process by enabling developers to leverage previously implemented modules, thereby increasing the speed and efficiency of subsequent WSN implementations. The adapters ensure communication between tinyDSM and microcontroller peripherals or external hardware blocks, such as sensors, and facilitate the integration of new modules. The emphasis on edge computing enables data processing at the node level, reducing network traffic and increasing resource efficiency.
Keywords: komputeryzacja; przyrządy pomiarowe; informatyka; technologie informacyjne